THE DEPELOPMENT OF HAEMONCHUS CONTORTUS EGGS TO FIRST STAGE LARVAE IN LIQUID MEDIA IN SITU - Wirawan, I Gusti Komang Oka; Yuliani, Ni Sri; Toelle, Novianti Neliyani; Suryawati, . (Buletin Veteriner Udayana, 2022)
Haemonchus contortus is a highly pathogenic worm in sheep and goats. A study was conducted to determine the in situ percentage of the development of H. contortus worm eggs at the first-stage larvae (L 1 ) in water. This research treatment was repeated   5 times in one group with a duration of 10 days and each group used 8 female H. contortus worms. These worm eggs are counted using the McMaster method. The prepared worm samples were ground, immersed in 5 mL of pro-injection aqua (pH 7.0), and filtered using a tea filter. Research procedure: 1.5 mL of suspension was collected, placed into a tube and treated according to the procedure. Each tube, covered with aluminium foil that has holes 15 to 20, was placed on pasture for 48 h (05:00 – 24:00); where ambient temperature was recorded every four hour. Research variable include: percentage of hatched worm eggs in the immersion group. The hatchability percentage = ((the difference between numbers of worm eggs before and after treatment): (those before treatment) x 100)). Data were tabulated and analysed descriptively. The results showed that: the percentage of the total average development of the L 1 H. contortus worm eggs was 26.5%. Conclusion: the percentage of egg development of H. contortus in situ was 26.5%. The influencing factors are ambient temperature, pH, humidity, culture media, and egg abnormalities. It is recommended to extend the breeding time in the media in the hope that the percentage yield is more optimal.